Pelatihan Eco-Print: Pemanfaatan Tanaman Rumahan untuk Merangsang Produktivitas Masyarakat Desa Manduro MG: Eco-Print Training: Utilization of Home Plants to Stimulate Productivity of Manduro MG Village Community - Kusrini, Nurul Azizah Ria; Agustyarini, Yhasinta; Sandy, Priatna; Idris, Idris (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Manduro MG Village has limited natural resources, and most of its residents work as factory employees. Although they have small plots of land around their homes, they have not utilized them optimally. Therefore, the community service team implemented the Asset-Based Community-Driven Development (ABCD) method to raise awareness and enhance residents' skills in utilizing available assets. This program was conducted through Eco-print training, a natural dyeing technique using leaves, twigs, and flowers to create eco-friendly products. The training consisted of four sessions: introduction, pounding technique demonstration, hands-on product creation, and digital marketing training using Canva and social media. The evaluation measured skill improvement through direct observation and discussion, as well as observations of production and marketing progress. Results showed that 85% of participants successfully created standard-quality products, and some initiated Eco-print-based businesses. This program is expected to foster new SMEs and boost the economic productivity of Manduro MG Village.